Intracontinental deformation of the western Ordos Basin in North China and sandstone‐type uranium mineralization: Constraints from AFT chronology of the Helan Mountain. (2nd September 2021) - Nie, Fengjun; Yan, Zhaobin; Wang, Yannan; Zhang, Jin; Xia, Fei; Yang, Dongguang; Wang, Sili; Chen, Mengya; Peng, Yunbiao; Miao, Aisheng
Abstract : Apatite fission track (AFT) sampled from Helan Mountain, of the western Ordos Basin, North China shows that the study area located in the western part of the North China Craton (NCC) has undergone four‐stage exhumation since Mesozoic time, that is, Late Jurassic to Early Cretaceous, Late Cretaceous, Early Cenozoic, and post‐late Miocene. Helan Mountain had slowly uplifted and eroded from the Late Jurassic to the beginning of the Cenozoic. The intensive deformation within NCC is attributable dynamically to the gently angular subduction of the Pacific Plate under the Eurasian Plate (EP). Helan Mountain has undergone sinistral strike‐slipping with a 60‐km maximum displacement caused by the collision of the southeast margin of EP during the Late Cretaceous. The Early Cenozoic tectonic event in the study area is respondent to collision between the Indian Plate and Eurasian Plate, whereas, the post‐late Miocene event is likely related to the eastward extension of Tibet Plateau. Based on the available AFT ages, the partial annealing zone for the palaeo‐Helan Mountain is ascertained to elevation ~1, 200 m to ~2, 100 m. The tectonic events occurring from Mesozoic to Cenozoic in Helan Mountain is directly related to the plate margin tectonism and representative for the intracontinental deformation of Eurasian Plate convergence. The sandstone‐type uranium deposits in the western margin thrust belt of Ordos Basin are related to the Late Jurassic to Early Cretaceous and Late Cretaceous exhumation events. Immediately after the host rock, the Zhiluo Formation sedimentation during the Middle Jurassic, the Late Jurassic ~ Late Cretaceous exhumations resulted in north–south‐trending anticlines, synclines, and thrust faults; meanwhile, the Zhiluo Formation was uplifted to the surface and infiltrated by uranium‐bearing oxidized fluids originated from the Helan Mountain. Uranium deposits were formed in both east and west limbs of folds. Finally, uranium mineralization ceased since the Cenozoic because the Yinchuan and Hetao faulted grabens have separated the Helan Mountain provenance from the western margin thrust belt. Abstract : This study focuses on the relationship between sandstone‐type uranium mineralization in a basin and its marginal uplift. From the Middle Jurassic to the Late Cretaceous, sedimentation and mineralization of the host rock, Zhiluo Formation (Fm) in Ordos Basin took place in chronological sequence. At first stage, the Zhiluo Fm was deposited in braided fluvial environment from 168 to 163 Ma. At second stage, the Helan Shan and West Marginal Thrust Belt (WMTB) in Ordos Basin were uplifted and exhumed under the regional compression during 163/135~120 Ma. At third stage, the uranium‐bearing oxidized fluid (UOF) sourced from Helan Shan penetrated the Zhiluo Fm sandstone and resulted in a large‐scale uranium mineralization in WMTB during 135–120 Ma to ~95–75 Ma period. At fourth stage, the mineralization was terminated due to the formation of the Yinchuan Graben since ~40 Ma.